Procedures Experiments using Photogrammetric Method - Inne Chaysalina; Achmad Syarief; Meirina Triharini (Eduvest - Journal of Universal Studies, 2021)
Tangible objects are actual objects that can be touched and have a physical form. Therefore, the existence of tangible objects cannot be separated from the potential of damage and even disappearance. At the same time, tangible objects can be an essential source of research and can be a historical source that needs to be preserved. With the development of technology, objects can be recorded in digital forms, 2D Documentation, such as photos and videos, and increasingly sophisticated technology makes object recording developed in 3D Documentation. An easy method with good data quality results is photogrammetric. The implementation of the photogrammetric method has many advantages, some of which are straightforward procedures, portable equipment, and relatively low prices. This study uses a qualitative method based on photogrammetric experiments with various lighting settings and different needs. The results of this research are trying to breakdown of photogrammetric procedures that can applied according to field conditions.